2012
DOI: 10.1111/j.1529-8027.2012.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic neuropathy: new paradigms, new promise

Abstract: Idiopathic neuropathy, now designated as chronic idiopathic axonal polyneuropathy (CIAP), is a major public health problem in the United States. The disorder affects an estimated 5-8 million Americans, comprising about one-third of patients with neuropathy, based on data from referral centers. Typically, patients develop symptoms in the sixth decade or older. The onset is insidious, with numbness, paresthesias, and pain appearing over months to years. Although strength is generally preserved, the sensory loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 47 publications
1
31
0
2
Order By: Relevance
“…35,36 Cases with late onset have reduced likelihood of finding a genetic cause, highlighting the longstanding polygenic enigma of chronic idiopathic axonal polyneuropathy (CIAP). 37 In this study, no patients with CIAP phenotypes had pathologic mutations, consistent with evidence-based practice guidelines discouraging genetic testing in them. 12 However, accurately determining the age at onset can be difficult and careful clinical judgment is emphasized.…”
mentioning
confidence: 68%
“…35,36 Cases with late onset have reduced likelihood of finding a genetic cause, highlighting the longstanding polygenic enigma of chronic idiopathic axonal polyneuropathy (CIAP). 37 In this study, no patients with CIAP phenotypes had pathologic mutations, consistent with evidence-based practice guidelines discouraging genetic testing in them. 12 However, accurately determining the age at onset can be difficult and careful clinical judgment is emphasized.…”
mentioning
confidence: 68%
“…CIAP is diagnosed by slowly progressive distal symmetric sensory or sensorimotor polyneuropathy [52]. NCS shows reduced amplitude [46], EMG examination shows abnormalities, laboratory tests show normal values, and skin biopsy confirms the diagnosis of CIAP by evaluation of density and structure of epidermal nerve fibers [46,52]. Erdmann et al (2010) found that 69% of CIAP patients have pain [52].…”
Section: Diabetic Neuropathymentioning
confidence: 99%
“…Risk factors that contribute to development of CIAP include hypertension, impaired glucose tolerance, obesity, hypercholesterolemia, and environmental toxins [47,[49][50][51]. All these risk factors cause oxidative stress [46]. CIAP is diagnosed by slowly progressive distal symmetric sensory or sensorimotor polyneuropathy [52].…”
Section: Diabetic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…This is true to a greater degree in patients with small fiber neuropathy where 50% or more of patients have idiopathic neuropathy (Periquet et al, 1999;Venkataramana et al, 2005;De Sousa et al, 2006) (Table 1). Singer et al (2012) discussed current research being done in idiopathic neuropathy. The only treatment that we have for peripheral neuropathy is when we can treat the identifiable cause.…”
mentioning
confidence: 99%